2020
DOI: 10.3390/medicines7060033
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations of Inflammatory Bowel Disease and the Role of Non-Invasive Surrogate Markers of Disease Activity

Abstract: Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), can be associated with several extra-intestinal manifestations requiring a multidisciplinary management both in terms of work-up and therapy. Oral lesions are common in patients with IBD, with a prevalence ranging from 5% to 50%. These can represent an oral location of IBD as well as a side-effect of drugs used to treat the intestinal disease. Oral manifestations, occurring in patients with IBD, can be divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 70 publications
(73 reference statements)
3
29
1
5
Order By: Relevance
“…The prevalence of oral lesions is reported in a range from 5% to 50%. [73][74][75] In the pediatric patient population, a prevalence of 7%-23% has been reported. 75 Oral lesions are reported to be more common in patients with CD and more prevalent in children.…”
Section: Skin Extraintestinal Manifestations In Inflammatory Bowel Diseasementioning
confidence: 99%
“…The prevalence of oral lesions is reported in a range from 5% to 50%. [73][74][75] In the pediatric patient population, a prevalence of 7%-23% has been reported. 75 Oral lesions are reported to be more common in patients with CD and more prevalent in children.…”
Section: Skin Extraintestinal Manifestations In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Lesions of the oral cavity may be painful and may lead to impaired oral function or to psychological misbalances due to esthetic involvement [ 9 ]. Lesions of the oral mucosa may seem more severe during a period of disease exacerbation but 30% of patients, especially of pediatric age, present active oral manifestations during IBD remission [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a group of 1649 pediatric IBD patients, 97 children presented with extraintestinal manifestations, 21% of which were aphthous stomatitis [ 3 ]. In another retrospective study, 24% of children with IBD presented dermatological manifestations, 18% of which were aphthous stomatitis [ 10 ]. In a study from Iran, oral aphthous lesions were identified in 13% of patients with CD vs 6% of UC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenesis of oral manifestations of IBD remains unclear. Currently research reported on the potential role of microbiota in the pathogenesis of IBD and its oral location, it has been proposed that dysbiosis (term that means imbalance within the bacterial community) of salivary microbiota (with relative abundance of Streptococcus, Prevotella, Haemophilus, and Veillonella) may play a crucial role 13 . Severe IBD has a less diverse microbiota with fewer commensal microbiota communities and more opportunistic pathogenic bacteria originating from the oral cavity or respiratory tract 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Angular cheilitis is characterized by erythema at the corners of the mouth with or without painful fissures and sores. It can be a consequence of anemia or fungal and bacterial infections 13 . In our research prevalence of unspecific inflammatory manifestations in the oral cavity were (35.3%) for children with CD and (18.7%) for children with UC (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%